Mitigation of human‐induced vertical vibrations of footbridges through crowd flow control. Issue 12 (8th October 2018) - Venuti, Fiammetta; Reggio, Anna
Summary: Due to their lightweight, slenderness, and extremely low structural damping, footbridges are prone to human‐induced vibrations. As a consequence, vibration mitigation strategies, mainly tuned mass dampers (TMDs), have been often implemented to reduce their dynamic response under pedestrian loading. In this study, a novel strategy towards the mitigation of human‐induced vertical vibrations of footbridges is investigated: instead of acting on the structure, it is proposed to act on the source of excitation, realising what can be suitably defined as crowd flow control . Crowd flow control aims at altering the distribution of the crowd density and, as a consequence, of the walking velocity and step frequency. The dynamic loading exerted by the pedestrians is thus modified and the input energy transferred to the footbridge is reduced. Crowd flow control can be easily and quickly implemented via either permanent (e.g., benches or light poles) or temporary (e.g., Jersey barriers) obstacles located along the footbridge span and is expected to be cheaper than competing vibration mitigation strategies. The study is carried out by means of numerical simulations. A microscopic model of crowd dynamics is used to generate pedestrian trajectories and velocities, whose corresponding force signals are built and then applied to the single degree of freedom model of an ideal footbridge. The performance of crowd flow control is investigated by considering different obstacles locations, by assessing effectiveness and robustness against variations in the pedestrian excitation and by establishing comparisons with a linear viscoelastic TMD. An interpretation of the results from an energy perspective is finally provided.